Bullying and its Impact on Individual Mental Health: A Literature Review - Ramadani, Novi; Umairha, Nadia (Al'Adzkiya Journal, 2023)
Bullying is any form of oppression or violence, which is carried out intentionally by individuals or groups. Bullying always causes victims, especially students in elementary, junior high, and high school environments. This study aims to determine the effect of bullying which has a significant impact on the mental health of individuals in the educational environment who are victims. The author also discusses the types of bullying, the impact of bullying, and the social support received by victims. This research is a literature review by conducting a literature search in several online databases such as PubMed, Google Scholar, and PsycINFO. The results of this study, bullying is not only done in person but also online, not only about physical but also can be verbal and the impact of bullying in the form of depression, anxiety, eating disorders, sleep disorders, and decreased self-esteem. Therefore, it is important for us to understand the impact of bullying on mental health and take action to prevent it.